Median nerve mobilization techniques in the treatment of carpal tunnel syndrome: A systematic review - Lim, Y.; Chee, D.; Girdler, Sonya; Lee, H. (Elsevier, 2017)
© 2017 Hanley & Belfus. Study Design: Systematic review. Introduction: Median nerve mobilization is one of the interventions used in the treatment of carpal tunnel syndrome (CTS). However, it is uncertain how many types of mobilization techniques are described in the current literature or the relative effectiveness of these techniques in treating CTS. Purpose of the Study: The aim of this review was to describe the types and effectiveness of median nerve mobilization techniques studied in the CTS literature. Methods: Electronic searches of 5 databases and manual searches of references lists located randomized controlled trials studies published between 2000 and April 2015. Quality appraisal for each study was conducted using the Standard Quality Assessment Criteria for Evaluating Primary Research Papers from a Variety of Fields by 2 independent reviewers. Results: Nine randomized controlled trial studies describing various median nerve mobilization techniques used in the treatment of CTS were included. All studies were rated as of "adequate", "good", or "strong" quality for the Standard Quality Assessment Criteria. Three techniques of median nerve mobilization were described. Treatment outcomes included measures of electrodiagnostic testing, functional performance, pain, physical examination, sensation, and strength. Standardized mean differences for the treatment outcomes ranged from very small to large (0.05-1.71). Conclusion: The findings are inconclusive regarding the effectiveness of each mobilization technique due to methodological limitations in the current body of research. Therefore, there is a clear need for high-quality controlled studies to examine various approaches to median nerve mobilization techniques in the treatment of CTS. Level of evidence: 2a.